Velikii voin Albanii Skanderbeg . The Great Warrior Skanderbeg - Yutkevich, Sergei (Mosfilm, 1953)
Duration: 02:00:00 Set in the 15th century, the film is a historical epic introducing the Albanian leader Skanderbeg (Skenderbeu aka Georgi Kastriot) who fought against the Ottomans and is considered to be a prominent national hero. The film is a Soviet-Albanian co-production, Akaki Khrava stars as a legendary Albanian patriot. In 1954, the film won the Grand Prize and Special Mention for the direction at the Cannes Film Festival.